Membentuk Kepribadian Murid Melalui Sifat-Sifat Terpuji Dalam Ajaran Islam Yang Berdampak Terhadap Peningkatan Prestasi Belajar - Nurhusna, S. (AKADEMIK: Jurnal Mahasiswa Humanis, 2021)
This research aims at analyzing and revealing the influence of parents’ care and religion teachers competence toward the development of Islamic values within students SMAN 4 (Senior high schools) Tangerang South City. Within the family, teaching Islamic values to children is a mandate and a responsibility parents with must hold. At school, on the other hand, the mandate lies with the school especially with the religion teacher who have tr responsibility to educate and guide students in order for thr values of Islamic to develop as is expected by parents Care from parents and competence of religion teachers are factors that are expected to give influence to the development of Islamic values within students. This research is a qualitative descriptive research using survey as the technique of data collection. The population of this research was all students of all SMA (Seniority high schools) in the sub-discrete of Tangerang south city. The sample was decided using proportional random sampling technique which resulted in the selection of –perkelas--. The independent variables of this research are the care from parents and the competence of religion teachers. Where as the dependent variable is the development of Islamic values within students. The data was tested for its reliability and validity, and was processed using dato normalization to test the influencing valuables; multiple linear regression method was used along with t-test and f-test to measure its significance. The research showed that parents care has significantly positive influence to the development of Islamic values within student of senior high schools in the sub-district of Tangerang south. Between the independent variables it was revealed that religion teachers competence has more influence then parents care does with the correlation coefficient of 0,595.